2005
DOI: 10.4049/jimmunol.175.4.2301
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Glial Cell Line-Derived Neurotrophic Factor Family Ligands and Their Receptors on Human Immune Cells

Abstract: There is increasing evidence that factors originally identified due to their neurotrophic activity also function within the immune system. This study focused on the related molecules glial cell line-derived neurotrophic factor (GDNF) and neurturin (NTN) as well as their receptors. GDNF and NTN signaling is mediated by a two-component receptor: a signal-transducing component, RET, which is shared by both ligands, and a ligand-specific binding component, GFRα-1 (higher GDNF affinity) or GFRα-2 (higher NTN affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 33 publications
5
64
0
Order By: Relevance
“…However, additional mechanisms are certainly involved. NGF can also lead to the indirect sensitization of primary afferents through the activation of immune cells (Lewin et al, 1994;Bennett et al, 1998;Lambiase et al, 2004;Vargas-Leal et al, 2005). Furthermore, both neurotrophins and GDNF family members activate transcription in sensory neurons that may lead to lasting changes in nociceptor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional mechanisms are certainly involved. NGF can also lead to the indirect sensitization of primary afferents through the activation of immune cells (Lewin et al, 1994;Bennett et al, 1998;Lambiase et al, 2004;Vargas-Leal et al, 2005). Furthermore, both neurotrophins and GDNF family members activate transcription in sensory neurons that may lead to lasting changes in nociceptor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GDNF receptors RET and GFR␣1-4 are expressed in CD4 ϩ and CD8 ϩ T cells, B cells, and monocytes, indicating a potential effect of GDNF on immune cells. Although it has been demonstrated that RET/GFR␣ signaling is dispensable for thymic T cell development (3), application of GDNF led to a decrease in TNF-␣ secretion in monocytes (59). Furthermore, GDNF directly influences the blood-brain barrier by upregulation of the tight junction protein claudin 5, which leads to barrier-stabilizing effects (50,63).…”
Section: Gdnf Directly Promotes Barrier Maturation and Proliferation mentioning
confidence: 99%
“…Additionally, a protective effect on the intestinal epithelial barrier was reported in an animal model of IBD that points to a potential role of GDNF in the pathogenesis of these complex diseases (59). In this review we aim to summarize and discuss the current knowledge on the effects of GDNF in intestinal barrier regulation and its potential role in the contribution to the pathogenesis of IBD.…”
mentioning
confidence: 99%
“…Other neuropeptide and cytokine production could be dependant on NTN and influence the inflammatory response like IL-1, capsaicin, or calcitonin generelated peptide (33). NTN was also shown to be produced by human immune cells (monocytes, B cells, and T cells) (12). Another hypothesis could be that NTN is expressed by immune cells and delivers an antiinflammatory message that reduces migration or survival of eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…Another member of this family, NTN, exerts its effects through a multicomponent receptor system consisting of the GDNF family receptor a 2 (GFRa-2) and the proto-oncogene RET (10,11). It was previously shown that NTN is produced by human immune cells: monocytes, B cells, and T cells (12). NTN is also structurally similar to TGF-b, and it was demonstrated that TGF-b 1 is a protective cytokine in airway inflammation (13).…”
mentioning
confidence: 99%